Proof

For every sets

X

P

(Src

f

) and

Y

P

(Dst

f

)

X

[(

FCD

)(

RLD

)

in

f

]

Y

(

Src

f

X

×

RLD

Dst

f

Y

)

6≍

(

RLD

)

in

f

RLD

(Src

f

;Dst

f

)

(

X

×

Y

)

6≍

[ n

a

×

RLD

b

|

a

atoms 1

F

(Src

f

)

, b

atoms 1

F

(Dst

f

)

, a

×

FCD

b

f

o

(*)

a

atoms 1

F

(Src

f

)

, b

atoms 1

F

(Dst

f

)

: (

a

×

FCD

b

f

∧ ↑

RLD

(Src

f

;Dst

f

)

(

X

×

Y

)

6≍

(

a

×

RLD

b

))

a

atoms 1

F

(Src

f

)

, b

atoms 1

F

(Dst

f

)

: (

a

[

f

]

b

a

⊆↑

Src

f

X

b

⊆↑

Dst

f

Y

)

X

[

f

]

Y.

* theorem 53 in [15].

Thus (

FCD

)(

RLD

)

in

f

=

f

.

Remark 7

The above theorem allows to represent funcoids as reloids.

Obvious 29.

(

RLD

)

in

(

A ×

FCD

B

) =

A ×

RLD

B

for every f.o.

A

,

B

.

Conjecture 15

(

RLD

)

out

I

FCD

A

=

I

RLD

A

for every f.o.

A

.

Exercise 1

Prove that generally (

RLD

)

in

I

FCD

A

6

=

I

RLD

A

.

Conjecture 16

dom(

RLD

)

in

f

= dom

f

and

im(

RLD

)

in

f

= im

f

for every fun-

coid

f

.

Proposition 38

dom (

f

|

A

) =

A ∩

dom

f

for every reloid

f

and f.o.

A ∈

F

(Src

f

)

.

Proof

dom (

f

|

A

) = dom (

FCD

)

f

|

A

= dom ((

FCD

)

f

)

|

A

=

A ∩

dom (

FCD

)

f

=

A ∩

dom

f

.

Theorem 67

For every composable reloids

f

,

g

:

1. If

im

f

dom

g

then

im (

g

f

) = im

g

.

2. If

im

f

dom

g

then

dom (

g

f

) = dom

f

.

Proof

1. im (

g

f

) = im (

FCD

) (

g

f

) = im ((

FCD

)

g

(

FCD

)

f

) = im (

FCD

)

g

= im

g

.

2. Similar.

Conjecture 17

(

RLD

)

in

(

g

f

) = (

RLD

)

in

g

(

RLD

)

in

f

for every composable

funcoids

f

and

g

.

57